Stunting and its Determinants among Governmental Primary School Children in Egypt: A School-based Cross-sectional Study - Metwally , Ammal M.; El-Sonbaty, Marwa; El Etreby, Lobna A.; El-Din, Ebtissam M. Salah; Hamid, Nabih Abdel; Hussien, Hanan A.; Hassanin, Amal; Monir, Zeinab M. (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: In developing countries, stunting among children is a major public health concern. It affects all aspects of children’s lives; its effects are not constrained to physical wellbeing but reach out to mental, social, and spiritual wellbeing. AIM: The aim of this study is to determine the prevalence of stunting in some of the Egyptian governmental primary school children and its nutritional and socioeconomic determinants. METHODS: A cross-sectional observational study was conducted on primary school children aged 6–12 years. General demographic, socioeconomic, and anthropometric data, as well as dietary pattern, were collected. RESULTS: Out of 1740 children, 7.8% were stunted. Not eating eggs and dairy products had the most profound effect on stunting in children (p < 0.001). Not having meals on time, skipping breakfast, and having <3 meals per day were predictors of stunting (p = 0.003, p = 0.00, and p = 0.008, respectively). Mother’s education (p = 0.005) followed by family income (p = 0.007) was the most affecting social factors. CONCLUSION: There are many nutritional factors associated with stunting as skipping breakfast, not having meals on time, and having <3 meals per day. Scarcity in nutritive foods as eggs and dairy products and increased soft drink intake can lead to stunting. There are many enabling social factors for stunting as mother’s education and family income. However, the effects of these factors can be modified by health awareness.